Menciptakan Sekolah Anti Kekerasan Melalui Pendampingan Tim Pencegahan dan Penanganan Kekerasan (TPPK) di SMPN 11 Makassar - Avelyn Pingkan Komuna; Nuraziza Aliah; Nemos Muhadar (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia is currently facing a child protection emergency, marked by a significant increase in cases of violence against children, particularly within educational institutions, up to the year 2023. As a strategic measure to strengthen child protection efforts, the government issued Ministerial Regulation of Education, Culture, Research, and Technology No. 46 of 2023 concerning the Prevention and Handling of Violence in Educational Units (PPKSP). This regulation mandates every educational institution to establish a Task Force for the Prevention and Handling of Violence (TPPK) and to implement systematic prevention programs. However, the implementation of this policy has not been optimal, as there are still educational institutions that lack adequate understanding of child protection and have not formed a TPPK, including SMP Negeri 11 Makassar. In response to this issue, an intervention in the form of a mentoring program for the establishment of a TPPK at the school is necessary to create a safe and violence-free learning environment. This activity is part of Universitas Terbuka’s community service program as a tangible contribution to supporting the prevention of violence against children in educational settings, particularly in the city of Makassar.